Political Violence and Law Reform in Turkey:: Securing the Human Rights of the Kurds? - Hughes, Edel (Journal of Conflict Studies, 2006)
ABSTRACT The article begins with an historical overview of the Kurds in Turkey and the background to the conflict in the southeast of the country. The second section examines the manner in which the conflict has been dealt with by the Turkish authorities and looks in particular at the effect the imposition of emergency rule and draconian anti-terrorism legislation has had on the enjoyment on human rights. The article concludes with an analysis of the impact of the reforms engendered by the European Union accession process.